False-positive serologies for acute hepatitis A and autoimmune hepatitis in a patient with acute Epstein–Barr virus infection - Valota, Marika (BMJ Case Rep, 2019)
Acute hepatitis remains a diagnostic challenge, and numerous infectious, metabolic and autoimmune diseases need to be effectively excluded. We present a case of a young woman with malaise, fever, jaundice and deranged liver function tests. Testing for Epstein–Barr virus (EBV) virus capsid antigen IgM/IgG was positive. Total IgG was elevated, along with positive serology for anti-hepatitis A virus (HAV)-IgM, antinuclear antibodies (ANAs) and soluble liver antigen (SLA) leading to the differential diagnosis of acute hepatitis A and autoimmune hepatitis. No specific treatment was started and liver function gradually improved. At week 4, HAV IgG and IgM were negative. At month 4, ANA and SLA were negative and total IgG normalised; EBV nuclear antigen became positive. Testing for EBV is an investigation required at baseline in acute hepatitis and physicians should carefully evaluate serological results, including those for viral and autoimmune hepatitis that may be falsely positive in infectious mononucleosis.